Elusive identities, enduring demands: the Haatis’ struggle for recognition in the trans-Giri region, Himachal Pradesh - Nilamber Chhetri (European Bulletin of Himalayan Research)
Practices and politics of group classification have provoked multiple contestations regarding social categories in postcolonial South Asia. The adoption of the colonial classificatory model has generated heated discussion over the veracity and tenability of these categories. The concomitant impact of this normative ethnological praxis has led to ethnogenesis of varied kinds across the regions. The logic of determining group boundaries by having recourse to cultural determinants has accentuated claims of authenticity as a tribal group in different regions. With this, the territorial basis of recognition has instantiated demands based on geographical congruity and has initiated identity claims on a performative scale. In this article, I examine the case of the Haatis in Himachal Pradesh to delineate the micropolitics of recognition struggles where cultural identity and territorial scale coalesce to reinvigorate the quest for classificatory justice.